„Aby czynić i działać społecznie, potrzeba wprzód znać drogi i cele, mieć obrachunki i programy”. O różnych płaszczyznach działalności ormiańskiego arcybiskupa Józefa Teodorowicza - Załęczny, Jolanta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
Artykuł koncentruje się na działalności społecznej arcybiskupa Józefa Teodorowicza (1864–1938). W latach 1902–1914 był posłem Sejmu Krajowego, członkiem Rady Szkolnej Krajowej, zasiadał w Izbie Panów w Wiedniu (1914–1918). W odrodzonej Polsce był posłem (1919–1922), a potem senatorem (1922–1923). Dużą wagę przykładał do edukacji młodego pokolenia. Był mocno zaangażowany w szerzenie oświaty. Występował w obronie prawa dzieci i młodzieży do nauczanie po polsku w każdym z trzech zaborów. Dostrzegał potrzebę kształcenia kobiet, zabiegał o szerzenie oświaty na wsi. Szczególnie dużo uwagi poświęcał sprawom wychowania w szkole i rodzinie. Patronował powstawaniu nowych szkół i organizacji.

The article focuses on the social activities of Archbishop Józef Teodorowicz (1864-1938). From 1902 to 1914, he served as a member of the National Parliament, the National School Council, and the House of Lords in Vienna (1914-1918). In the newly restored Poland, he was a member of parliament (1919-1922) and later a senator (1922-1923). He attached great importance to the education of the younger generation and was heavily involved in promoting education. He advocated for the right of children and youth to be taught in the Polish language in all three partitions. He recognized the need for educating women and worked to promote education in rural areas. He devoted significant attention to matters of education within schools and families, patronizing the establishment of new schools and organizations.
“To act and operate socially, it is necessary in advance to know the ways and goals, to have calculations and programs.” About the various levels of activity of Armenian Archbishop Józef Teodorowicz
Keywords: Ormianie; Lwów; patriotyzm; wychowanie; Teodorowicz; Armenians; Lviv; patriotism; education